2018
DOI: 10.4049/jimmunol.1701507
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis Virus Nonstructural Protein NS5 Induces RANTES Expression Dependent on the RNA-Dependent RNA Polymerase Activity

Abstract: Tick-borne encephalitis virus (TBEV) is one of the flaviviruses that targets the CNS and causes encephalitis in humans. The mechanism of TBEV that causes CNS destruction remains unclear. It has been reported that RANTES-mediated migration of human blood monocytes and T lymphocytes is specifically induced in the brain of mice infected with TBEV, which causes ensuing neuroinflammation and may contribute to brain destruction. However, the viral components responsible for RANTES induction and the underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 90 publications
(101 reference statements)
4
33
0
Order By: Relevance
“…On one hand, this helix is critical to both the JEV-mode and DENV3-mode of interface interactions by contributing the F349 and R353 residues (Fig 2A and 2B; Fig 3B). On the other hand, it is at the central region of a long stretch of conserved sequences (residues 341-366 in DENV2 NS5) that may also be related to NS5 nuclear localization, nuclear export, and interaction with another important viral protein NS3 [19,30,31], emphasizing its possible importance when not participating in the intra-molecular MTase-RdRP interactions. We propose that the largely rotational movement of the MTase from the JEV-mode conformations to the DENV3-mode conformations may utilize this highly conserved helix as a guiding track (S1 Movie).…”
Section: Plos Pathogensmentioning
confidence: 99%
“…On one hand, this helix is critical to both the JEV-mode and DENV3-mode of interface interactions by contributing the F349 and R353 residues (Fig 2A and 2B; Fig 3B). On the other hand, it is at the central region of a long stretch of conserved sequences (residues 341-366 in DENV2 NS5) that may also be related to NS5 nuclear localization, nuclear export, and interaction with another important viral protein NS3 [19,30,31], emphasizing its possible importance when not participating in the intra-molecular MTase-RdRP interactions. We propose that the largely rotational movement of the MTase from the JEV-mode conformations to the DENV3-mode conformations may utilize this highly conserved helix as a guiding track (S1 Movie).…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The siRNAs targeting vacuolar ATPase (VTPase, sc-42686), dynamin (sc-43736), Rab5 (sc-36344), and Rab7 (sc-29460), respectively, were purchased from Santa Cruz. T98G cells were transfected with the indicated siRNAs using a HiPerFect Transfection Reagent (Qiagen) according to the manufacturer's protocol (Zheng et al, 2018). Knockdown efficiency was measured by Western blot.…”
Section: Rna-mediated Interferencementioning
confidence: 99%
“…During TBEV infection of human astrocytes, the RLRs RIG-I and MDA5, but not TLR3, sense TBEV NS5 and activate IRF-3 signaling, which leads to the production of CCL5 (58). A recent study analyzing RNA expression profiles of TBEV infected human neuro-glia cultures, i.e., neuron and astrocyte cocultures, showed that in astrocytes the transcripts of Ddx58, Oas2, IFN-β, Mx1, Trim5a and Rasd2 were even more abundantly induced than in neurons (57).…”
Section: Discussionmentioning
confidence: 99%